De-implementing wisely: developing the evidence base to reduce low-value care - Grimshaw, Jeremy M; Patey, Andrea M; Kirkham, Kyle R; Hall, Amanda; Dowling, Shawn K; Rodondi, Nicolas; Ellen, Moriah; Kool, Tijn; van Dulmen, Simone A; Kerr, Eve A; Linklater, Stefanie; Levinson, Wendy; et al. (BMJ quality & safety, 2020)
Choosing Wisely (CW) campaigns globally have focused attention on the need to reduce low-value care, which can represent up to 30% of the costs of healthcare. Despite early enthusiasm for the CW initiative, few large-scale changes in rates of low-value care have been reported since the launch of these campaigns. Recent commentaries suggest that the focus of the campaign should be on implementation of evidence-based strategies to effectively reduce low-value care. This paper describes the Choosing Wisely De-Implementation Framework (CWDIF), a novel framework that builds on previous work in the field of implementation science and proposes a comprehensive approach to systematically reduce low-value care in both hospital and community settings and advance the science of de-implementation.The CWDIF consists of five phases: Phase 0, identification of potential areas of low-value healthcare; Phase 1, identification of local priorities for implementation of CW recommendations; Phase 2, identification of barriers to implementing CW recommendations and potential interventions to overcome these; Phase 3, rigorous evaluations of CW implementation programmes; Phase 4, spread of effective CW implementation programmes. We provide a worked example of applying the CWDIF to develop and evaluate an implementation programme to reduce unnecessary preoperative testing in healthy patients undergoing low-risk surgeries and to further develop the evidence base to reduce low-value care.